The Hidradenitis Suppurativa Foundation. Issue 6 (November 2021) - Ezekwe, Nneamaka; Parks-Miller, Angie; Hamzavi, Iltefat
Abstract : ABSTRACT: The Hidradenitis Suppurativa (HS) Foundation strives to improve the lives of people living with HS. To achieve that mission, the HS Foundation works through advocacy, education, and research. Our vision is to live in a world where no one suffers from HS. Read about what our organization has to offer.